(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2024)
The application of 3D geospatial information technology in road construction has emerged as a transformative approach to enhance efficiency, accuracy, and productivity. This research investigates the utilization of 3D geospatial data in the context of road infrastructure development within Edo State, Nigeria. The study employed several vital technologies: Global Navigation Satellite System (GNSS): Precise positioning for accurate data collection. Static Light Detection and Ranging (LiDAR): Capturing detailed elevation information. Unmanned Aerial Vehicles (UAVs) LiDAR: Aerial data acquisition. These technologies facilitated the creation of 3D terrain models representing actual topography. The accuracy of data obtained through static LiDAR and UAV LiDAR was within 0.025 meters in all three dimensions. Construction automation, enabled by 3D geospatial information, demonstrated significant productivity gains. Sensors installed on construction equipment allowed for real-time adjustments based on 3D models. Beyond road construction, this technology can be applied to other infrastructure projects, including tunnels, bridges, and urban development. Edo State can leverage 3D geospatial information to improve project planning and design.